2016
DOI: 10.15171/ijhpm.2016.38
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and Retention of Physicians in Primary Healthcare Facilities: A Qualitative Study From Abbottabad, Pakistan

Abstract: Background: Workforce motivation and retention is important for the functionality and quality of service delivery in health systems of developing countries. Despite huge primary healthcare (PHC) infrastructure, Pakistan's health indicators are not impressive; mainly because of under-utilization of facilities and low patient satisfaction. One of the major underlying issues is staff absenteeism. The study aimed to identify factors affecting retention and motivation of doctors working in PHC facilities of Pakista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(101 citation statements)
references
References 35 publications
2
95
0
4
Order By: Relevance
“…Decision of transfers are often beyond their control making such a job unpopular especially with women. [17] As urbanite residents, our study participants' reluctance to work anywhere other than within their own city was resolute.…”
Section: Peripheral Theme Ii: Cultural Normsmentioning
confidence: 83%
“…Decision of transfers are often beyond their control making such a job unpopular especially with women. [17] As urbanite residents, our study participants' reluctance to work anywhere other than within their own city was resolute.…”
Section: Peripheral Theme Ii: Cultural Normsmentioning
confidence: 83%
“…Research results of Alnıaçık et al (2012) showed that motivation had a positive correlation with organizational commitment and job satisfaction. A recent study by Shah et al (2016) identifi ed some of the factors that affected job motivation (adequate remuneration, good job environment, etc. ).…”
Section: Ključne Riječi: Zadovoljstvo Poslom Drvna I Papirna Industrmentioning
confidence: 99%
“…The reason for health care workers choosing family practice is mostly higher wages, and this finding is consistent with the findings in other studies . The administrators and medical staff indicated that salaries were higher in the FP period compared to the HC period, and this is consistent with the findings in previous studies .…”
Section: Discussionmentioning
confidence: 93%